2012
DOI: 10.1111/j.1365-2788.2011.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Carers' perspectives of a weight loss intervention for adults with intellectual disabilities and obesity: a qualitative study

Abstract: This study identified specific facilitators and barriers experienced by carers during the process of supporting obese adults with ID to lose weight. Future research could utilise these findings to inform appropriate and effective weight management interventions for individuals with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 42 publications
5
60
0
Order By: Relevance
“…Participants who had study partners that reported more hassles had higher weights at the end of the 18-month study, and those who had study partners who reported higher self-efficacy had greater weight loss at the end of the study. This is in agreement with previous research (17, 20, 34) that suggests a successful weight management intervention needs to reduce barriers for not only the participants but also for their caregivers. Spanos et al (20) suggests that, in order to reduce caregiver barriers, weight management interventions need to incorporate small, established staff teams that can follow the weight loss plan consistently and to establish better communication and cooperation between the staff within the same support team.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Participants who had study partners that reported more hassles had higher weights at the end of the 18-month study, and those who had study partners who reported higher self-efficacy had greater weight loss at the end of the study. This is in agreement with previous research (17, 20, 34) that suggests a successful weight management intervention needs to reduce barriers for not only the participants but also for their caregivers. Spanos et al (20) suggests that, in order to reduce caregiver barriers, weight management interventions need to incorporate small, established staff teams that can follow the weight loss plan consistently and to establish better communication and cooperation between the staff within the same support team.…”
Section: Discussionsupporting
confidence: 93%
“…While multiple study partners did not impact weight loss during the entire 18-month study, this finding still suggests that adults with IDD may benefit from having a consistent caregiver during a weight management intervention. Similarly, Spanos et al (20) reported that participants who are in homes with multiple staff would benefit from having consistent shift patterns and more one-on-one time allocated with the person they support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview data will be used to inform future outcome and intervention studies. Carer involvement has been shown to be important in lifestyle behaviour change for adults with intellectual disabilities [28, 53]. Interviews with family members will allow us to gain insight into the influence that family can have on lifestyle behaviours in young people with intellectual disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, families and carers play an important role in the lifestyle behaviours of an individual’s intellectual disabilities. Research has suggested that parents and carers’ own lack of motivation or time to be active can be a barrier to supporting an individual with intellectual disabilities to participate in physical activity [28]. Further, recent research [29] suggests that some paid carers and family members who were supporting individuals with intellectual disabilities to take part in a walking intervention rewarded walking and good behaviour with sweet treats and fizzy drinks.…”
Section: Introductionmentioning
confidence: 99%